2010
DOI: 10.1007/s00392-010-0227-6
|View full text |Cite
|
Sign up to set email alerts
|

New-onset versus chronic atrial fibrillation in acute myocardial infarction: differences in short- and long-term follow-up

Abstract: Our results indicate that patients with chronic AF had a higher incidence of in-hospital death than those with new-onset AF or without. Chronic AF includes a group of older and sicker patients than their counterparts with new-onset AF. Understanding these findings may ultimately lead to better care of patients with this arrhythmia to prevent the development of the underlying atrial substrate in chronic AF patients and to improve their otherwise worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 32 publications
3
13
1
10
Order By: Relevance
“…The most common type of AF in this study was new-onset AF accounting for almost half of the AF population followed by paroxysmal and chronic AF. Other, smaller studies have reported previous AF to be more common than new-onset AF during MI 6 14. AF in this study was also more common in patients with NSTEMI than in patients with STEMI.…”
Section: Discussioncontrasting
confidence: 41%
“…The most common type of AF in this study was new-onset AF accounting for almost half of the AF population followed by paroxysmal and chronic AF. Other, smaller studies have reported previous AF to be more common than new-onset AF during MI 6 14. AF in this study was also more common in patients with NSTEMI than in patients with STEMI.…”
Section: Discussioncontrasting
confidence: 41%
“…All of these factors lead to a decrease in cardiac output and an increase in left ventricular filling pressure [ 17 ]. Patients with pre-existing AF generally have greater cardiovascular disease burden and more co-morbidities than those without AF owing to AF being present for longer [ 18 , 19 ]. In contrast, patients with new-onset AF were relatively younger and had fewer co-morbidities than patients with pre-existing AF [ 4 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results from previous studies evaluating the prognostic significance of pre-existing and new-onset AF in patients with ACS are conflicting [ 8 11 , 18 , 21 ]. In a prospective multicenter study of 3393 patients with ACS, pre-existing AF was associated with a significantly higher risk of mortality (HR 1.4, 95% CI 1.01–1.99) than no AF, while new-onset AF was not [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence indicated that among patients with acute myocardial infarction, those with chronic AF had a higher in-hospital mortality rate than those with newly diagnosed AF or no AF. 12 Therefore, we carried out a systematic review and meta-analysis to investigate the effect of AF on clinical outcomes in patients with IS undergoing thrombolysis.…”
Section: Introductionmentioning
confidence: 99%